Energy efficient in-memory AES encryption based on nonvolatile domain-wall nanowire - Wang, Yuhao (2015)
The widely applied Advanced Encryption Standard (AES) encryption algorithm is critical in secure big-data storage. Data oriented applications have imposed high throughput and low power, i.e., energy efficiency (J/bit), requirements when applying AES encryption. This paper explores an in-memory AES encryption using the newly introduced domain-wall nanowire. We show that all AES operations can be fully mapped to a logic-in-memory architecture by non-volatile domain-wall nanowire, called DW-AES. The experimental results show that DW-AES can achieve the best energy efficiency of 24 pJ/bit, which is 9X and 6.5X times better than CMOS ASIC and memristive CMOL implementations, respectively. Under the same area budget, the proposed DW-AES exhibits 6.4X higher throughput and 29% power saving compared to a CMOS ASIC implementation; 1.7X higher throughput and 74% power reduction compared to a memristive CMOL implementation.